Hydrogen production by hydrolysis of sodium borohydride for PEM fuel cells feeding - Silva, R. A. (2010)
In this work, hydrogen is produced by a hydrolysis process that uses sodium borohydride as a hydrogen carrier and storage media. High purity hydrogen is obtained at low temperatures with high volumetric and gravimetric storage efficiencies; reaction products are non-toxic. The produced hydrogen can be supply on-demand at specified flow by tailor made developed catalyst. Hydrogen feeding to a low power fuel cell was accomplished. According to experimental conditions conversion rates of 100% are possible. Catalyst is demonstrated to be reusable.